2016
DOI: 10.1111/tra.12407
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin Trafficking for Tissue Morphogenesis: Control and Consequences

Abstract: Cadherin-based adherens junctions are critical for connecting cells in tissues. Regulated cadherin trafficking also makes these complexes amazingly dynamic, with permissive and instructive consequences on multicellular development. Here, we review how cadherin trafficking affects various forms of tissue morphogenesis from Drosophila and Caenorhabditis elegans to zebrafish, Xenopus and mouse. We describe how core trafficking machinery (such as clathrin, dynamin, Rab small G proteins and the exocyst complex) int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 100 publications
0
42
0
Order By: Relevance
“…Apically localized molecules play crucial roles during neural plate folding as scaffolding proteins that participate in the apical constriction of cells (Eom et al, 2011;Haigo et al, 2003;Hildebrand and Soriano, 1999;Morita et al, 2010;Nandadasa et al, 2009;Nishimura and Takeichi, 2008;Ossipova et al, 2014). For example, cadherins coordinate the cytoskeletal dynamics and cell-cell interactions necessary for tissue bending and morphogenesis (Nishimura and Takeichi, 2009;West and Harris, 2016). We discovered a molecular interaction among Folr1, C-cadherin and β-catenin.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Apically localized molecules play crucial roles during neural plate folding as scaffolding proteins that participate in the apical constriction of cells (Eom et al, 2011;Haigo et al, 2003;Hildebrand and Soriano, 1999;Morita et al, 2010;Nandadasa et al, 2009;Nishimura and Takeichi, 2008;Ossipova et al, 2014). For example, cadherins coordinate the cytoskeletal dynamics and cell-cell interactions necessary for tissue bending and morphogenesis (Nishimura and Takeichi, 2009;West and Harris, 2016). We discovered a molecular interaction among Folr1, C-cadherin and β-catenin.…”
Section: Discussionmentioning
confidence: 93%
“…Remodeling of adherens junctions between cells is crucial for tissue morphogenesis (Nishimura and Takeichi, 2009;West and Harris, 2016). C-cadherin is an important component of adherens junctions in X. laevis neural plate (Nandadasa et al, 2009).…”
Section: Molecular Knockdown Of Folate Receptor Hinders Neural Tube Cmentioning
confidence: 99%
“…Recent live-imaging studies have revealed the extent to which E-cadherin is actively turned over at adherens junctions, highlighting the extremely dynamic nature of intercellular adhesion, even in relatively stable epithelia (Kowalczyk and Nanes, 2012;West and Harris, 2016). In cases of collective epithelial cell migration, this continuous modulation of E-cadherin and other junctional components, such as catenins, is key to maintaining tissue integrity throughout cell movements.…”
Section: Adherens Junctions Cell Adhesion and Apico-basal Polaritymentioning
confidence: 99%
“…, 2014; Zhang et al. , 2014; West and Harris, 2016). This process is inhibited by p120-catenin, which binds to the cadherin tail and masks an endocytic motif in the juxtamembrane domain (Chiasson et al.…”
Section: Introductionmentioning
confidence: 99%